Simultaneous Determination of Different Anions in Milk Samples Using Ion Chromatography with Conductivity Detection - Destanoğlu, Orhan; Gümüş Yılmaz, Gülçin (The Turkish Chemical Society, 2016)
The description of a simple method for simultaneous determination of chloride, nitrate, sulfate, iodide, phosphate, thiocyanate, perchlorate, and orotic acid in milk samples was outlined. The method involves the use of dialysis cassettes for matrix elimination, followed by ion chromatography on a high capacity anion exchange column with suppressed conductivity detection. The novelty of dialysis process was that it did not need any chemical and organic solvent for elimination of macromolecules such as fat, carbohydrates and proteins from milk samples. External standard calibration curves for these analytes were linear with great correlation coefficients. The relative standard deviations of analyte concentrations were acceptable both inter-day and intra-day evaluations. Under optimized conditions, the limit of detection (Signal-to-Noise ratio = 3) for chloride, phosphate, thiocyanate, perchlorate, iodide, nitrate, sulfate, and orotate was found to be 0.012, 0.112, 0.140, 0.280, 0.312, 0.516, 0.520, and 0.840 mg L −1 , respectively. Significant results were obtained for various spiked milk samples with % recovery in the range of 93.88 - 109.75 %. The proposed method was successfully applied to milk samples collected from Istanbul markets. The advantages of the method described herein are reagent-free, simple, and reliable.
Keywords: Milk; Dialysis; Chloride; Nitrate; Sulfate; Iodide; Phosphate; Thiocyanate; Perchlorate; Orotic acid; Ion chromatography